Olive oils from Campos de Hellin (Spain) exhibit significant varietal differences in fatty acid composition, sterol fraction, and oxidative stability - Sena-Moreno, Estela; Alvarez-Orti, Manuel; Zied, Diego C. [UNESP]; Pardo-Gimenez, Arturo; Pardo, José E. (Wiley-Blackwell, 2015)
The Spanish region of Campos de Hellin (Albacete) is characterized by a wide range of olive varieties (Arbequina, Benizal, Cornicabra, Cuquillo, Injerta, Manzanilla Local, Manzanilla de Sevilla, Negrilla, Picual), which provides different physicochemical and sensory characteristics to the oils. Thus, the knowledge of these characteristics may help develop more balanced oils. Monovarietal virgin olive oils from the different varieties grown in this area were characterized from the physicochemical and sensory points of view during four consecutive years. Clear differences among the varieties were found when principal component analysis was applied to the data from the studied parameters. The varieties were grouped according to their oleic and linoleic acid content, oxidative stability, and campesterol and total sterols content. The differences were significant with a 95% confidence level. The variety effect on the oil characteristics was stronger than the effect of the crop year. Practical applications: Chemical and sensory characteristics of monovarietal virgin olive oils play an important role in the elaboration of blends. In olive-growing regions where there is more than one variety cultivated, the characterization of monovarietal oils could increase the value of the olive oil produced due to the development of more balanced oils tailored to the preferences of consumers. This work shows that the chemical and sensory differences between varieties make possible the elaboration of a new range of virgin olive oils. This could encourage the development and marketing of quality oils, and thus increase the competitiveness of the mills in the oil market.
Keywords: Crop year; Chemical composition; Monovarietal olive oil; Stability; Variety